Bediuzzaman Said Nursi’s methodology for da’wah: an overview of certain principles = منهجية بديع الزمان سعيد نورسي للدعوة: نظرة عامة على بعض المبادئ - Ushama, Thameem (The Journal of Risale-i Nur Studies, 2019)
This study presents approaches to daᶜwah as adopted and taught by Said Nursi to advance his restoration efforts. It also sheds light on the importance of their application in the present era. The paper reviews two distinct issues: [1] approaches Said Nursi used to confront and resolve social complexities, and [2] daᶜwah praxis in the modern age. The author also discusses complexities and challenges as presented by modern life styles. Special daᶜwah features are described including educational and political efforts as well as the nurturing of Islamic virtue with Nursi’s emphasis on those specific characteristics that inspire Muslim scholars to excel in daᶜwah activities. Nonetheless, it is impossible to thoroughly deliberate Nursi’s approaches and strategies in such a limited space. *************************************************************************************** إن هذه الدراسة تقدم الطرق التي تبعها في الدعوة وقام بتعليمها وذلك بغرض المضي قدما في مساعيه وجهوده للإصلاح، وتلقي هذه الدراسة الضوء كذلك على اهمية تطبيق ذلك على الحقبة الحاضرة، قامت الورقة باستعراض قضيتين مختلفتين (1) الوسائل التي استخدمها الإمام سعيد النورسي ليواجه التعقيدات الاجتماعية ومن ثم يجد لها الحلول و (2) تطبيقات الدعوة وتنزيلها في الواقع المعاصر، قام كاتب المقال ايضا بمناقشة التعقيدات والتحيات التي تتمثل من خلال اساليب الحياة المعاصرة، قامت الورقة بوصف مميزات وخصائص خاصة بالدعوة متضمنة الجهود التربوية والتعليمية والسياسية الى جانب تنشية الفضائل الاسلامية مع تركيز النورسي على هذه المميزات المحددة التي تلهم العلماء المسلمين لترقية الانشطة الدعوية، وبالرغم من هذا فانه من المستحيل ان يتتبع الباحث بصورة موسعة وسائل النورسي واستراتيجياته في مثل هذه المساحة المحدود